Harmonic Suppression Dual-band Dipole Antenna with Parasitic Elements and a Stub - A. B. Albishti; S A Hamzah; S M Shah; K N Ramli; N Abdullah; M S Zainal; L Audah; A Ubin; F C Seman; A K Anuar; S Z Sapuan; R Atan; M Esa; N N N Abd Malik (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2018)
A dual-band harmonic suppression dipole antenna suitable for energy harvesting system is presented in this paper. A linear dipole with two parasitic elements is designed and fabricated with a capability to eliminate the harmonic of higher order modes. At first, the antenna resonates at 900 MHz and 2.7 GHz. Therefore, a parasitic element is added into each of the dipole’s arm to tune the second frequency band to 2.4 GHz to fit into wireless application. However, the presence of two parasitic elements has generated an unwanted harmonic at 4.0 GHz. Thus, a stub has been integrated into the antenna’s terminal (feed line) to suppress the 4.0 GHz frequency. This technique is suitable for developing a multiband antenna with harmonic suppression. The antenna is fabricated on a FR-4 board with the size of 72×152 mm2 which operates efficiently at 0.8 GHz and 2.4 GHz which is suitable for wireless communication applications. The prototype can suppress the undesired harmful harmonics present within the frequency range of 3 to 5 GHz. The antenna has a good potential to be used in a rectenna system with a dual-band frequency operation but with better performance. Simulation and measurement results obtained are in a good agreement, which have confirmed the proposed design concept.